Transcriptomics data for muscle development in Goats - Yu Pei; Rongsheng Xi; Wenmeng Jiang; Peng Huang; Mei Liu (Scientific Data)
Abstract Goats play a significant role in global livestock production and are highly valued for their meat, which is both nutritious and easily digestible. The longissimus dorsi and biceps femoris muscles are not only critical for goat locomotion and weight support but also serve as primary determinants of meat quality and nutritional value. To elucidate the gene expression patterns and genetic regulatory mechanisms underlying goat muscle development, this study collected longissimus dorsi and biceps femoris muscles from pregnant goats in late gestation and their fetuses. Full-length transcriptome sequencing was performed with the Oxford Nanopore Technologies (ONT) platform, generating 169,768,069 valid reads, 127,954,092 of which were successfully aligned to the reference genome, with an average N50 value of 1042.29. Data processing and assembly identified 58,092 full-length transcripts, with 50,338 annotated based on databases such as NR, Uniprot, GO, KEGG, and Pfam. Notably, this study identified 89,468 alternative splicing (AS) events across seven categories and predicted 5,538 potential long non-coding RNAs (lncRNAs) in two muscle tissues using three prediction methods. These findings substantially enhance the goat full-length transcriptome database and provide crucial data for uncovering functional genes, epigenetic regulation, and early nutritional intervention strategies relevant to goat meat quality. The open sharing of this dataset aims to advance the academic understanding of goat muscle development and its genetic basis, thereby promoting precision breeding strategies and the sustainable development of meat goat production.